Comparison of Recombinant Tissue Factor Pathway Inhibitors Expressed in Human SK Hepatoma, Mouse C127, Baby Hamster Kidney, and Chinese Hamster Ovary Cells - Wun, Tze-Chein; Kretzmer, Kuniko K; Palmier, Mark O; Day, Kathleen C; Huang, Margaret D; Welsch, Dean J; Lewis, Charles; Wolfe, Richard A; Zobel, James F; Lange, Gary W; Frazier, Ronald B; Bild, Gary S; Peel, Michelle A; Shell, Robert E; Horn, Nancy A; Junger, Kurt D; Foy, Barbara A; Gustafson, Mark E; Leimgruber, Richard M; Novotny, William F; Broze, George J, Jr; Pyla, Yvonne E; Hippenmeyer, Paul J; Warren, Thomas G (Thrombosis and Haemostasis, 1992)
Recombinant tissue factor pathway inhibitor (rTFPI) has been expressed in four mammalian expression systems using human SK hepatoma, mouse C127, baby hamster kidney (BHK), and Chinese hamster ovary (CHO) cells as hosts. On sodium dodecyl sulfate polyacrylamide gel electrophoresis, the immunoaffinity purified rTFPIs all show broad bands and the mean molecular weight of SK hepatoma and C127 rTFPIs (Mr ~ 38,000) appear larger than those of BHK and CHO rTFPIs (Mr ~ 35,000). All these proteins inhibit factor Xa and appear to bind factor Xa with 1:1 stoichiometry. The ability of these proteins to inhibit tissue factor-induced coagulation in plasma was examined using a prothrombin time assay. The relative activities of SK rTFPI:C127 rTFPI:BHK rTFPI:CHO rTFPI were found to be 28:15:2.1:1. By Western blot using specific antisera against the amino- and carboxy-termini of TFPI as probes, it is found that all the immunoaffinity purified rTFPIs possess approximately equal amounts of the amino terminus, but the C127 and BHK rTFPIs are deficient in carboxy terminus and the CHO rTFPI is essentially devoid of this region of the protein. Mono S chromatography allowed separation of the full-length and the truncated molecules with high and low anticoagulant activities, respectively. The above results suggest that proteolysis of the carboxy terminus of TFPI occurs to different extent when TFPI is expressed in different cells and that the carboxy terminal region of the TFPI molecule is important for the inhibition of tissue factor-induced coagulation. Recombinant and non-recombinant SK hepatoma cells appear to produce TFPI with the least amount of proteolysis compared with other cell systems tested and SK TFPI functionally resembles TFPI circulating in the blood.